The Use of Mind Mapping Technique to Improve Learning Outcomes of Fathu Makkah Material for Students at MI Plus Ma’arif Nu Jatinegara - Cahyaningsih, Wiji; Supu, Wati; Wahidiyah; Cholipah, Wahyui; Nabila, Wilpa (MANDAILING GLOBAL EDUKASIA, 2025)
This Classroom Action Research aims to improve students' learning outcomes on the Fathu Makkah material through the application of the Mind Mapping technique at MI Plus Ma'arif NU Jatinegara. The background of this study is the low understanding of students on narrative Islamic history material, so a more effective and interesting learning strategy is needed. The Mind Mapping technique was chosen because it can help students organize information visually, improve memory, and facilitate systematic understanding of concepts. This research was conducted in two cycles with the stages of planning, implementation, observation, and reflection. The subjects of the study were grade V students of MI Plus Ma'arif NU Jatinegara. Data were collected through learning outcome tests, observations, and interviews, then analyzed descriptively qualitatively and quantitatively. The results of the study showed an increase in student learning outcomes after the application of the Mind Mapping technique, marked by an increase in the average class value and student activity in learning. Thus, the use of the Mind Mapping technique has proven effective in improving learning outcomes on the Fathu Makkah material. It is recommended that teachers apply this technique as an alternative in teaching Islamic history material to make it more interesting and easier for students to understand.